THE USE OF PARTICIPATION OF POINT SYSTEM (PPS) METHOD IN WRITING - Syahban Mada Ali (JURNAL EDUKASI NONFORMAL, 2021)
The objective of the research is to find out the use of Participation Point System (PPS) method effective in improving the Students’ writing at the second semester students English Education Study Program at Tomakaka University of Mamuju. This research took place at University of Tomakaka Mamuju which the researcher used pre-experimental. Population of research was the second grade students of English Education Study Program in academic year 2020/2021. Sample of the research was 20 students that take by purposive sampling technique. The researcher used writing test in paragraphs form as instrument of the research. Result of data analysis showed that t-table value at n-1 = 20-1=19 (at significant level α = 0,05) was 2.09 and t-test value was 8.30. It showed t-test was higher than t-table, it meant that null hypothesis was rejected and alternative hypothesis was accepted. Therefore, the researcher summarized that the use of Participation Point System (PPS) method could improve the students’ writing at the second semester students of English Education Study Program at Tomakaka University of Mamuju. It was supported result of students’ mean score at pre-test and post-test. Which mean score of pre-test was 67.15 (Fair score) improved to 78.50 (good score) at the post-test.